Answer:
LAST OPTION: [tex]x^9[/tex]
Step-by-step explanation:
For this exercise it is important to remember the Power of a power property, which states that:
[tex](a^m)^n=a^{mn}[/tex]
The expression given in the exercise is:
[tex](x^\frac{3}{2})^6[/tex]
Therefore, in order to simplify it, you must apply the Power of a power property explained before.
Then, you get the following expression:
[tex]=x^{(\frac{3}{2}*6)}=x^{(\frac{3*6}{2})}=x^{\frac{18}{2}}=x^9[/tex]
As you can notice, the expression obtained matches with the expression provided in the last option.